Modifications of academic competences and intelligence in a university grade (2021)
The aim of the study was to analyze differences in intelligence, academic competences, and academic achievement by gender and academic course in sports science university students. To reach the study aim we analyzed in 267 (226 males and 41 females) first and last year students’ degree the variables of intelligence (Reasoning scale of the Primary Mental Abilities Test), academic achievement and self-perception of 40 academic competences (30 general competences and 10 specific competences). We found how last year degree students presented higher general and specific competences than first year students, not presenting differences in intelligence and academic achievement. Female students presented higher academic achievement and higher values in some general and specific competences but not in intelligence.